Temperature Dependent Switching Behavior of BFN Thin Films: a Wide Band Gap Semiconductor - Devang D. Shah; P.K. Mehta; M.S. Desai; C.J. Panchal (Журнал нано- та електронної фізики)
The thin film of complex perovskite Ba(Fe0.5Nb0.5)O3 (BFN) was prepared through Pulsed Laser Deposition (PLD) technique. XRD and AFM studies show single cubic phase with well developed nano size grains of BFN compound. Swift Heavy Ion (SHI) irradiation on BFN of O+7 ions up to 1 × 1013 ions per cc fluence does not show any crystal or morphological structural changes in the film, signifying materials stability up to the above ion dose. BFN compound exhibit its band gap in wide band semiconductor region (3.53 eV). A characteristic negative temperature coefficient of resistance (NTCR) to positive temperature coefficient of resistance (PTCR) transition of large magnitude at ~ 350 °C makes BFN a promising candidate for electrical/magnetic switching device.